ANALISIS FRAMING DALAM PEMBERITAAN MEDIA - muzakkir muzakkir (Universitas Teuku Umar, 2017)
Framing analysis is the latest version of the discourse analysis approach, especially for analyzingmedia texts. Framing analysis as a method of media content analysis, classified as a new version.It evolved in unison with the views of the constructors. This paradigm has its own position andoutlook towards the media. News in the view of social construction, is not an event or fact in areal sense. Here reality is not just simply taken for granted as news. It is a product of interactionbetween journalists and facts. In the process of internalization of journalists hit by reality. Realityis observed by journalists and absorbed in the consciousness of journalists. In the process ofexternalization, journalists throw themselves into meaningful reality. Conceptions of facts areexpressed to see reality. The result of the news is the product of the process of interaction anddialectics. There are two aspects to framing that, First; pick facts, second; write down facts.Keywords: Framing Analysis, Newspaper Frame, Impact of News